2021
DOI: 10.3389/fcell.2021.673995
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Mouse Model to Study the Noonan Syndrome Gene Lztr1 in the Telencephalon

Abstract: The leucine zipper-like transcriptional regulator 1 (Lztr1) is a BTB-Kelch domain protein involved in RAS/MAPK pathway regulation. Mutations in LZTR1 are associated with cancers and Noonan syndrome, the most common RASopathy. The expression and function of Lztr1 in the developing brain remains poorly understood. Here we show that Lztr1 is expressed in distinct regions of the telencephalon, the most anterior region of the forebrain. Lztr1 expression was robust in the cortex, amygdala, hippocampus, and oligodend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…LZTR1 had been studied mostly with respect to their functions in the nervous system, such as schwanmomatosis [ 9 ], autism [ 10 ], and Noonan syndrome [ 11 , 12 ]. However, in 2017, Cancer Genome Atlas Research Network published the results of the comprehensive and integrative genomic characterization in hepatocellular carcinoma (HCC), and they found that LZTR1 was the significantly mutated gene in HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…LZTR1 had been studied mostly with respect to their functions in the nervous system, such as schwanmomatosis [ 9 ], autism [ 10 ], and Noonan syndrome [ 11 , 12 ]. However, in 2017, Cancer Genome Atlas Research Network published the results of the comprehensive and integrative genomic characterization in hepatocellular carcinoma (HCC), and they found that LZTR1 was the significantly mutated gene in HCC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%